The role and importance of ornament in contemporary cultural space (on example of Kazakh painting of XX – beginning of XXI centuries) - Khazbulatov, A. R.; Boldykova, Z. B. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2016)
The purpose of the article is to study ethno-cultural and ideological content of ornament as graphic dominant of kazakh painting. All sustanaible ornamental elements of visual analogy (“camel trail”, “spider”, “broken horn”, “horns”, etc.), contain deep symbolic level. According to the authors, the depth of the sacred meaning of ornamentology is present in the best paintings of Kazakhstan authors, beginning from Kasteev. The evolution of professional fine arts of Kazakhstan from the very beginning was aimed at preserving unique peculiarities of traditional culture. The analysis of some of the works of contemporary artists of Kazakhstan (N. Zhirenchiev, K.-G.Karzhasov H. Abdykalykov V. Gvozdev (Shege) N.Bazhenova, N.Bube, Z. Mukhamedzhanov) demonstrate creative possibilities of filling the plot with sacral worldview constructs of Kazakh traditional culture with the help of ornamentology.